Pengaruh Stress Kerja Terhadap Turnover Intention Karyawan Pada PT. Central Mega Kencana di Jakarta - Nurjati Sugiharto; Andriani Lubis (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of work stress on employee turnover intention at PT. Central Mega Kencana in Jakarta. The research method used is quantitative. The sample in this study were employees of PT. Central Mega Kencana in Jakarta, whose number was determined using the slovin formula and obtained representative results totaling 95 people. The sampling method in this study uses probability sampling with simple random sampling technique. The data analysis technique in this study used simple linear regression with the statistical program SPSS version 24. The results showed that the variable work stress has a significant effect on employee turnover intention at PT. Central Mega Kencana in Jakarta, this is evident from the results of the hypothesis test between work stress on employee performance employee turnover intention at PT. Central Mega Kencana obtained tcount > ttable (13.675 > 1.986) (H1 accepted). Based on the results of the analysis of the coefficient of determination, a result of 66.8% is obtained, which means that the contribution of work stress contributes to the variable turnover intention of employees of PT. Central Mega Kencana amounted to 66.8, the remaining 33.2% was influenced by other factors